Impact of Prolonged Cycle Length Resulting From Conversion of Atrial Fibrillation to Atrial Tachycardia on Ablation Outcome in Persistent Atrial Fibrillation Ablation - Jialing He; Guoshu Yang; Duan Luo; Yongxin Yang; Guijun He; Xianchen Yang; Zhen Zhang (Hindawi-Wiley, 2024)
Conclusions: Upon termination of persistent AF into AT during ablation, it was found that CL prolongation beyond 42.5 ms was associated with improved freedom from arrhythmia.